Implikasi Undang-Undang Nomor 25 Tahun 2008 Tentang Pembentukan Kota Sungai Penuh Terhadap Pengalihan Aset - Kusuma, Adinoor; Bustanuddin , Bustanuddin (Limbago: Journal of Constitutional Law, 2024)
Abstract This study aimed to find out about the delay in the agreement in Kerinci Regency Government and Sungai Penuh City Government and how the balance of assets between the Kerinci Regency Government and Sungai Penuh City Government. Sungai Penuh City is one of the two cities that were expanded in Jambi Province. This city was formed based on Law No. 25 of 2008 concerning the Establishment of Sungai Penuh City in Jambi Province. This expansion followed by the rights and responsibilities of the parent region to the regional expansion. One of those forms of diversion is an asset. In Law No. 25 of 2008 also explains that these assets are carried out no later than five years after the inauguration of the mayor. However, until 2022, the assets have not been fully handed over. This research conducted using the Juridical Empirical method. The problem analysis was carried out by processing library data and field data by interviewing respondents and informants related to regional asset management. The result of this study indicated the applicable legal provisions indicate that the implementation is not fully implemented due to different provisions of Article 13 (7) letter a and Article 14 of  law 25 of 2008. The other reason is the absence of funds from the center for the Kerinci Regency Government in the construction of the new capital. The volition of the law was not carried out by the Kerinci Regency Government and the Sungai Penuh City Government. Provisions concerning the Minister of an asset have been regulated in Domestic Decree Number 42 of 2001 concerning the Delivery of Goods and Receivables in a Newly Formed Region. It is suggested to the Governor of Jambi Province to be more firm in resolving problems and constraints in these assets, because it is the Governor's obligation as the representative of the Central Government to resolve the problems that occur. The author also recommends that the Central Government provide funds for the development of the Kerinci Regency Government. Keywords: Implications, Regional Assets, Transfer of Assets Abstrak Penelitian bertujuan untuk mengetahui implikasi keterlambatan pengalihan aset terhadap Pemerintah Kabupaten Kerinci dan Pemerintahan Kota Sungai Penuh, serta strategi penyelesaiannya. Meskipun Undang-Undang Nomor 25 Tahun 2008 menetapkan batas waktu lima tahun sejak pelantikan walikota, penyerahan aset masih belum diserahkan sepenuhnya hingga tahun 2022. Metode Yuridis Empiris digunakan dalam penelitian ini dengan mengolah data dari kepustakaan dan data lapangan dengan cara mewawancarai responden yang berkaitan dengan pengelolaan aset daerah. Hasil penelitian menunjukkan bahwa adanya perbedaan penafsiran terhadap ketentuan hukum, khususnya Pasal 13 Ayat (7) huruf a dan Pasal 14 Undang-Undang Nomor 25 Tahun 2008, menjadi penyebab utama kelambanan proses penyerahan aset. Ditambah tidak adanya dana dari pusat untuk Pemerintah Kabupaten Kerinci dalam pembangunan ibukota baru. Kehendak Undang-Undang tidak dijalankan oleh Pemerintah Kabupaten Kerinci dan Pemerintah Kota Sungai Penuh. Disarankan agar Gubernur Provinsi Jambi mengambil tindakan tegas dalam menyelesaikan permasalahan ini, mengingat kewajiban sebagai perwakilan Pemerintah Pusat. Selain itu, Pemerintah Pusat juga perlu mengalokasikan dana untuk mendukung pembangunan Pemerintah Kabupaten Kerinci. Langkah-langkah ini diharapkan dapat mempercepat penyelesaian aset dan meningkatkan efektivitas pemerintahan di daerah tersebut. Kata kunci: Implikasi, Aset Daerah, Pengalihan Aset